Association of vitamin D receptor genotype with leprosy type. - Roy, S; Frodsham, A; Saha, B; Hazra, S; Mascie-Taylor, C; Hill, A (1999)
Host genetic factors including major histocompatibility complex (MHC) polymorphisms influence both susceptibility to leprosy per se and also to leprosy type. Non-MHC genes may play an important role, but such genes remain undefined. The influence of two non-MHC candidate genes was assessed in a case-control study of Bengali leprosy patients from Calcutta. Recent studies have implicated variation in the vitamin D receptor (VDR) gene in susceptibility to several diseases, including osteoporosis and pulmonary tuberculosis. In this population, homozygotes for the alternate alleles of the VDR polymorphism are associated, respectively, with lepromatous and tuberculoid leprosy. The NRAMP1 (natural resistance associated macrophage protein 1) gene may influence human mycobacterial disease susceptibility based on studies with the murine homologue Nramp1. However, no significant association was found between NRAMP1 and leprosy susceptibility. This study suggests that the VDR polymorphism may influence susceptibility to some diseases by affecting the type and the strength of the host immune response.